Dynamics of a retreating ice sheet : a LiDAR study in Värmland, SW Sweden - Goodship, Alastair; Alexanderson, Helena (GFF, 2020)
Värmland in south western Sweden lies across the established zone of marine-terrestrial transition of the Scandinavian Ice Sheet (SIS) margin. The region lies inside the Younger Dryas maximum limit reached at 12.7 cal ka BP and the area of rapid final SIS retreat from 11.5 cal ka BP. LiDAR data across Värmland allows more detailed observation and analysis of glacial landforms formed during this stage than previously possible. This study synthesises geomorphological mapping performed on highly detailed digital elevation models (DEMs) and field observations across the region around Torsby in northern Värmland to reconstruct the dynamics of the ice sheet as it retreated. Several landforms that developed during deglaciation are identified and clearly reflect the change from a marine to terrestrially terminating ice margin. Ice-marginal deltas suggest a slowing of retreat at the point of marine-terrestrial transition. Increased topographic control on ice-sheet flow, pattern of drainage and ice sheet decay is indicated by the distribution of streamlined terrain, eskers, and outwash material. Hummocky terrain across low ground and incised valleys suggest persistence of ice in topographic lows beyond the retreat of the main ice front. Combined analysis of identified landforms allows a model for the pattern of retreat to be produced that traces the retreating ice sheet margin in far greater detail than previously has been possible in this area. This provides important data for understanding the final retreat of the SIS and details processes likely occurring beneath the margin of the Greenland Ice Sheet today.